2015
DOI: 10.3391/bir.2015.4.2.08
|View full text |Cite
|
Sign up to set email alerts
|

First report on the occurrence of invasive black-chin tilapia Sarotherodon melanotheron (Ruppell, 1852) in Manila Bay and of Mayan cichlid Cichlasoma urophthalmus (Gunther, 1892) in the Philippines

Abstract: Codium fragile subsp. fragile (Suringar) Hariot is a large, dichotomously branched green alga that has invaded many temperate locations around the globe. Despite its wide distribution and pest status, there are few accounts of Codium fragile subsp. fragile that provide morphological descriptions, including illustrations, for comparison. In 2008, a seaweed sample suspected to be Codium fragile subsp. fragile was collected from Albany, Western Australia. As this taxon superficially resembles other local erect an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…In addition, the Mayan cichlid, Mayaheros urophthalmus, (and hybrids of this species), which is endemic to the Atlantic slope of Central America, has been traded as an aquarium fish worldwide (Nico et al 2007). It has been documented in some parts of Southeast Asia, including Singapore, Sulawesi in Indonesia, around Manila Bay in the Philippines and the lowermost Chao Phraya River basin in Thailand (Nico et al 2007;Herder et al 2012;Kwik et al 2013;Ordoñez et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the Mayan cichlid, Mayaheros urophthalmus, (and hybrids of this species), which is endemic to the Atlantic slope of Central America, has been traded as an aquarium fish worldwide (Nico et al 2007). It has been documented in some parts of Southeast Asia, including Singapore, Sulawesi in Indonesia, around Manila Bay in the Philippines and the lowermost Chao Phraya River basin in Thailand (Nico et al 2007;Herder et al 2012;Kwik et al 2013;Ordoñez et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Tilapia species, including S. melanotheron, have been extensively introduced outside of their native range and often established feral populations. This also holds for S. melanotheron, which is, among others, found in the Philippines [9,18], Florida [19] and Hawaii [20]. As most tilapia introductions have been poorly documented, the correct identity of feral populations often remains unknown.…”
Section: Atchakpa Water Reservoirmentioning
confidence: 91%
“…Nile tilapia is currently rare whereas it was very common in the 1990s. Sarotherodon melanotheron is known to be invasive, i.e., it has the potential to spread widely, reproduce rapidly and persist in a new environment with a large range of impacts [9,10]. Knowing the correct identity of an invasive species is an important prerequisite for its efficient management.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis involved 11 nucleotide sequences. Ordoñez et al (2015) reported the presence of blackchin tilapia, Sarotherodon melanotheron, in the coastal waters of Manila Bay and the occurrence of Mayan cichlid, Cichlosoma urophthalmus, in Hagonoy, Bulacan for its range expansion and for the negative impacts of its existence due to the competitive interactions. The current infestation of Midas cichlid in Laguna de Bay is considered to be similar to the introduction of the Mayan cichlid and the blackchin tilapia.…”
Section: Midas Cichlid Amphilophus Citrinellusmentioning
confidence: 99%